Triage for Malnutrition Risk among Pediatric and Adolescent Outpatients with Cystic Fibrosis, Using a Disease-Specific Tool - Dimitrios Poulimeneas; Maria G. Grammatikopoulou; Argyri Petrocheilou; Athanasios G. Kaditis; Tonia Vassilakou (MDPI AG, 2020)
Malnutrition prevails in considerable proportions of children with Cystic Fibrosis (CF), and is often associated with adverse outcomes. For this, routine screening for malnutrition is pivotal. In the present cross-sectional study, we aimed to assess the risk for malnutrition in pediatric outpatients with CF. A total of 76 outpatients (44 girls, 11.9 ± 3.9 years old, 39.5% adolescents) were recruited and anthropometric, clinical, dietary and respiratory measures were collected. All outpatients were screened for malnutrition risk with a validated disease-specific instrument. Most children exhibited a low risk for malnutrition (78.9%), whereas none of the participants were characterized as having a high malnutrition risk. In the total sample, malnutrition risk was positively associated with age (r = 0.369, p = 0.001), and inversely related to the body mass index (r = −0.684, p < 0.001), height z-score (r = −0.264, p = 0.021), and forced expiratory volume (FEV1%, r = −0.616, p < 0.001). Those classified as having a low malnutrition risk were younger (p = 0.004), heavier (p < 0.001) and taller (p = 0.009) than their counterparts with a moderate risk. On the other hand, patients in the moderate risk group were more likely pubertal (p = 0.034), with a reduced mid-upper arm fat area (p = 0.011), and worse pulmonary function (p < 0.001). Interestingly, none of the children attaining ideal body weight were classified as having a moderate malnutrition. risk, whereas 37.5% of the patients allocated at the moderate risk group exhibited physiological lung function. In this cohort of outpatients with CF that were predominantly well-nourished and attained physiological lung function, malnutrition risk was identified only in small proportions of the sample. Our data support that patients that are older, pubertal, or have diminished fat mass are at greater risk for malnutrition.